Lessons from polio eradication: a synthesis of implementation strategies for global health services delivery from a scoping review - Neel, Abigail H.; Olateju, Adetoun; Peters, Michael A.; Schleiff, Meike; Alonge, Olakunle (Frontiers in Health Services, 2024)
IntroductionThere is limited guidance on strategies for delivering complex global health programs. We synthesized available evidence on implementation strategies and outcomes utilized in the global polio eradication initiative (GPEI) across low and middle-income country (LMIC) settings.MethodsWe nested our scoping review into a literature review conducted as part of a parent study, STRIPE. This review systematically searched PubMed for articles between 1 January 1988 and 25 April 2018 using polio search terms. Strategies from included studies were organized according to the Expert Recommendations for Implementing Change (ERIC) framework, specified using Proctor's framework, and linked to various outcomes (implementation, services delivery, impact).Results152 unique articles fulfilled our inclusion criteria (from 1,885 articles included in the parent study). Only 43 out of the 152 articles described a suitable quantitative study design for evaluating outcomes. We extracted 66 outcomes from the 43 unique studies. Study publication dates ranged from 1989 to 2018 and represented diverse country settings. The most common implementation strategies were developing mechanisms for feedback, monitoring, and evaluation (n = 69); increasing awareness among the population (n = 58); involving stakeholders, workers, and consumers in the implementation efforts (n = 46); conducting workshops (n = 33); using mass media (n = 31); and building robust record systems to capture outcomes (n = 31). Coverage (n = 13) and morbidity (n = 12) were the most frequently identified outcomes, followed by effectiveness (n = 9) and fidelity (n = 6). Feasibility and sustainability were rarely evaluated.ConclusionsThis review provides a catalogue of implementation strategies and outcomes relevant for advancing global health services delivery in LMICs drawing from the GPEI. Implementation strategies reviewed were poorly described and not adequately linked to outcomes. It calls for additional implementation research to unravel the mechanisms of implementation strategies and their effectiveness, and adaptation of the ERIC framework in LMICs.